2020
DOI: 10.3390/nu12030617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lutein and Astaxanthin Intake on the Improvement of Cognitive Functions among Healthy Adults: A Systematic Review of Randomized Controlled Trials

Abstract: Background: Fruits and vegetables are generally rich in antioxidants such as carotenoids. Consumption of carotenoids is expected to have benefits on cognitive functions in humans. However, previous randomized controlled trials (RCT) using carotenoids have reported inconsistent results. Therefore, this systematic review (SR) aimed to summarize the effect of carotenoid intake on cognitive functions in humans. Method: PubMed, Cochrane Library, Web of Science, and PsychoINFO were searched for research papers on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 79 publications
(222 reference statements)
0
26
0
Order By: Relevance
“…The methodological quality ratings of the studies were conducted based on previous studies [ 18 , 33 ]. The quality assessment scores ranged from 7 to 10 (see the Supplementary Table S4 ), indicating that all studies had adequate methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodological quality ratings of the studies were conducted based on previous studies [ 18 , 33 ]. The quality assessment scores ranged from 7 to 10 (see the Supplementary Table S4 ), indicating that all studies had adequate methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to consider the potential biological mechanisms underlying the effects of lutein on the human brain. Based on the previous hypothesis [ 18 ], we inferred the mechanisms by which lutein and its isomers affect brain activity and structure. Lutein and its isomer have antioxidant and anti-inflammatory effects in vivo [ 34 ] and traverse the blood-brain barrier [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of each study was assessed using the modified Delphi list [ 34 ]. These quality assessment criteria were based on previous systematic review papers [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…El-Agamy et al have shown the significant effect of ASX as a protective shield to doxorubicin which induces the impairment of cognitive functions [46]. A systematic review of RCTs demonstrated that in middle-aged adults, ASX significantly improved verbal episodic memory performance [47].…”
Section: Brain Healthmentioning
confidence: 99%